2019
DOI: 10.1103/physrevb.100.085426
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface-mediated anisotropic radiative heat transfer between nanoparticles

Abstract: Metasurfaces, the two-dimensional (2D) counterpart of metamaterials, have recently attracted a great attention due to their amazing properties such as negative refraction, hyperbolic dispersion, manipulation of the evanescent spectrum. In this work, we propose a theory model for the near field radiative heat transfer (NFRHT) between two nanoparticles in the presence of an anisotropic metasurface. Specifically, we set the metasurface as an array of graphene strips (GS) since it is an ideal platform to implement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Moreover, the amplification is sorely confined near the interface of the substrate, due to the surface characteristics of graphene surface plasmon polaritons (SPPs).The lack of the connecting between the particles and the substrate, and the nature of SPPs both restrict the relay effect.Graphene exhibits intriguing electronic properties including the presence of strongly confined SPPs which can be excited to transport energy in photonic channels [13,14]. This has been exploited for a more efficient RHT between hybrid periodic structures [15] and between nanoparticles [16]. Recently, by using multilayer structures, the RHT between NPs has been shown to be further increased thanks to a resonant coupling between the substrate surface modes and the NPs resonances [17].…”
mentioning
confidence: 99%
“…Moreover, the amplification is sorely confined near the interface of the substrate, due to the surface characteristics of graphene surface plasmon polaritons (SPPs).The lack of the connecting between the particles and the substrate, and the nature of SPPs both restrict the relay effect.Graphene exhibits intriguing electronic properties including the presence of strongly confined SPPs which can be excited to transport energy in photonic channels [13,14]. This has been exploited for a more efficient RHT between hybrid periodic structures [15] and between nanoparticles [16]. Recently, by using multilayer structures, the RHT between NPs has been shown to be further increased thanks to a resonant coupling between the substrate surface modes and the NPs resonances [17].…”
mentioning
confidence: 99%
“…Here, we will focus on the dipole model only, which is the theoretical workhorse of many recent works, because of its conceptional and numerical simplicity. For example, using this model it could be shown that the heat transfer between two dipolar objects can be enhanced by the presence of a substrate or more general third objects supporting surface waves like phonon polaritonic media [16][17][18][19][20], graphene [18], Moiré bilayer graphene [21], or hyperbolic media [22,23]. For non-reciprocal media even more interesting many-body effects were demonstrated like persistent heat currents and fluxes [24][25][26][27], giant magnetic resistances [28,29], Hall and anomalous Hall effect [30,31], circular polarized emission and thermal angular momentum and spin [25,32,33] as well as non-reciprocal near-field diodes [34,35] or spin-related directional thermal emission [36].…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuational electrodynamics theory developed by Rytov et al [1] is the basic theoretical framework to analyze NFRHT. NFRHT between two planar surfaces [2][3][4][5][6][7][8], two isolated nanoparticles [9][10][11], two spheres [12], one dipole and surface [13], two nanoparticles above a substrate [14][15][16][17], and between two nanoparticles separated by a multilayer plate [18] were investigated theoretically recently in such framework. The theory has been set in a general framework, and it is now possible to calculate the NFRHT between two or many bodies of arbitrary shape and dielectric permittivity using a general scattering matrix method [19,20], which was then applied to the many-body system with planar geometry [21].…”
Section: Introductionmentioning
confidence: 99%